2020
DOI: 10.31932/jees.v3i2.698
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Motivation-Regulation in Master Students’ Academic Reading

Abstract: Motivation is a paramount aspect in the learning process. It is a drive that encourages students to achieve better learning results. In the process of accomplishing the learning task, students might encounter difficulties that can demotivate them. Therefore, motivation-regulation is needed to maintain students’ motivation in completing the task. Many studies have been done to investigate master students’ academic reading. Yet, little research has explored master students' motivation-regulation in academic read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Moreover, P1 articulated that the activities in KWL strategy drove her to expand her knowledge in order to understand a certain passage. Indeed, reading activity requires students to tailor ideas stated by the author and information known by students (Diasti & Mbato, 2020). This finding is also supported by Dieu (2016) who found that KWL strategy improve students' academic achievement as it drives students to connect between their background knowledge and information stated in the articles.…”
Section: The Role Of Kwl Strategy In Elf Students' Reading Comprehensionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, P1 articulated that the activities in KWL strategy drove her to expand her knowledge in order to understand a certain passage. Indeed, reading activity requires students to tailor ideas stated by the author and information known by students (Diasti & Mbato, 2020). This finding is also supported by Dieu (2016) who found that KWL strategy improve students' academic achievement as it drives students to connect between their background knowledge and information stated in the articles.…”
Section: The Role Of Kwl Strategy In Elf Students' Reading Comprehensionmentioning
confidence: 82%
“…Moreover, reading English text adds more challenges to EFL students as they are accustomed to read reading text in their first language (Fitriani, 2014;Riadil, 2020). Reading involves intricate processes since students not only decode the meaning of the text but also connect between their prior knowledge and new information stated by the author (Tampubolon, 2017;Septiyana, Safitri, Aminatun, & Muliyah, 2019;Diasti & Mbato, 2020;Manihuruk, 2020;Pardede, 2022). However, connecting ideas in the reading passage, finding out specific information, and relating topics to background knowledge contribute to the main challenges faced by EFL students (Riadil, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Three prior research about students' motivation-regulation has been done previously (Diasti & Mbato, 2020b, 2020aMbato, 2013b). Diasti & Mbato (2020) First, interest enhancement is a strategy to boost participants' interest and intrinsic motivation in completing the task.…”
Section: Discussionmentioning
confidence: 99%
“…The first study was conducted by Bria and Mbato (2019) uncovering that a great number of Indonesian university EFL learners had progressively transformed into more confident and competent L2 readers after making use of varied metacognitive reading strategies. In another identical study, Diasti and Mbato (2020) strongly suggested L2 reading instructors to inculcating more robust self-efficacy within EFL learners, improve learners' reading interest in the target language, and corroborate learners' positive emotions in reading to fully escalate their target language reading competencies into more advanced levels. Hamanda and Takaki (2021) highly advocated Japanese EFL teachers provoke more positively-sound L2 reading classroom learning climates in the presence of diverse learners to increase their motivation in reading and degrade their foreign language reading anxiety gradually.…”
Section: Introductionmentioning
confidence: 96%